O jato de ar quente como estímulo punidor em rattus norvegicus - CARVALHO NETO, Marcus Bentes de (2014)
In experimental research on aversive control, electric shock has been predominantly used as a punisher stimulus. The present work describes the use of an apparatus that produces a hot air blast which can be an alternative stimulus to be used in research on aversive contingencies. The punishing function of the hot air blast was evaluated in both continuous (CRF) and intermittent (FR3) schedules and, in both cases, a partial suppression (98,4% and 71,15%, respectively) of the lever press responding was found, after a history of the continuous reinforcement. Suppression was bigger when the punishing stimulus was applied continuously and these data corroborate the data obtained with electric shock, described in the literature. Both the apparatus and the stimulus seemed to be appropriate from a technical and scientific perspective and the apparatus may become an attractive alternative from a financial standpoint.